2018
DOI: 10.1037/abn0000349
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal twin study of callous-unemotional traits during childhood.

Abstract: Previous research indicates that genetic factors largely account for the stability of callous-unemotional (CU) traits in adolescence. However, the genetic-environmental etiology of the development of CU traits has not been extensively investigated in childhood, despite work showing the reliable measurement and stability of CU traits from a young age. The aim of this study was to investigate the temporal pattern of genetic and environmental etiology of CU traits across primary school, from school entry (7 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…We have documented the genetic and environmental contributions to a variety of behavioral, educational, and health outcomes, as well as their associations, including different forms and functions of aggressive behaviors, such as reactive versus proactive versus social aggression (Brendgen et al, 2005(Brendgen et al, , 2006Paquin et al, 2017), early physical aggression and language (Dionne et al, 2003), early numeracy and later achievement in mathematics (Garon-Carrier et al, 2017), early sleep patterns and language development (Dionne et al, 2011;Touchette et al, 2013), attention-deficit/ hyperactivity and reading (Plourde et al, 2015(Plourde et al, , 2017, gambling and substance use (Vitaro et al, 2014(Vitaro et al, , 2018, callous-unemotional traits and fear recognition (Petitclerc et al, 2019), as well as more basic endophenotypes such as cortisol (Ouellet-Morin et al, 2016) and response inhibition (Schachar et al, 2011). We also showed that the stability of various social behaviors, such as disregard for rules (a central component of early opposition), physical aggression, callous-unemotional traits, and shyness, was more highly, and often quite substantially associated with genetic factors than their episodic manifestations (Henry, Dionne, Viding, Petitclerc et al, 2018;Lacourse et al, 2014;Morneau-Vaillancourt et al, 2019;Petitclerc et al, 2011).…”
Section: Scientific Contributionssupporting
confidence: 51%
“…We have documented the genetic and environmental contributions to a variety of behavioral, educational, and health outcomes, as well as their associations, including different forms and functions of aggressive behaviors, such as reactive versus proactive versus social aggression (Brendgen et al, 2005(Brendgen et al, , 2006Paquin et al, 2017), early physical aggression and language (Dionne et al, 2003), early numeracy and later achievement in mathematics (Garon-Carrier et al, 2017), early sleep patterns and language development (Dionne et al, 2011;Touchette et al, 2013), attention-deficit/ hyperactivity and reading (Plourde et al, 2015(Plourde et al, , 2017, gambling and substance use (Vitaro et al, 2014(Vitaro et al, , 2018, callous-unemotional traits and fear recognition (Petitclerc et al, 2019), as well as more basic endophenotypes such as cortisol (Ouellet-Morin et al, 2016) and response inhibition (Schachar et al, 2011). We also showed that the stability of various social behaviors, such as disregard for rules (a central component of early opposition), physical aggression, callous-unemotional traits, and shyness, was more highly, and often quite substantially associated with genetic factors than their episodic manifestations (Henry, Dionne, Viding, Petitclerc et al, 2018;Lacourse et al, 2014;Morneau-Vaillancourt et al, 2019;Petitclerc et al, 2011).…”
Section: Scientific Contributionssupporting
confidence: 51%
“…Two others were from the Antisocial Process Screening Device (APSD; Frick & Hare, ): ‘he/she did not keep promises’, ‘he/she used or conned others’. Additional work has supported a one‐factor structure at each wave that was time‐invariant (this material is featured in Henry et al., ). Mean scores were computed at each wave (a high mean score indicates high CU traits).…”
Section: Methodsmentioning
confidence: 93%
“…These findings are in line with earlier work in adolescence (Forsman et al, 2008) and leave open the possibility of distinct genetic effects on the intercept and slope of CU traits. Henry et al (2018) also showed that nonshared environmental influences were mostly age-specific and did not detect shared environmental influences on CU traits in their sample.…”
Section: Introductionmentioning
confidence: 89%